Analisis Faktor-Faktor yang Mempengaruhi Ketidakteraturan Pengelolaan Keuangan UMKM pada Sektor Katering di Kecamatan Mulyorejo - Savira Anjelin; Azra Maharani Yasita; Agustin Cintya Masita; Chesta Fillail Adabi; Tries Ellia Sandari (Jurnal Ilmiah Manajemen, Ekonomi dan Akuntansi, 2026)
In Indonesia, Micro, Small, and Medium Enterprises (MSMEs) are crucial for driving national economic development, particularly within the broad and prevalent micro-enterprise segment. However, in practice, financial management in micro-enterprises often exhibits variations that can impact business performance and sustainability. This study aims to identify and examine the factors that contribute to differences in financial management in MSMEs, particularly in the catering sector in Mulyorejo Regency. A qualitative descriptive method was used through observation, in-depth interviews, and documentation of micro-enterprise participants. The results indicate that these differences arise from several significant factors, including inadequate financial literacy, a lack of an organized record-keeping system, a tendency to combine personal and business finances, and an ineffective internal control and oversight system. Furthermore, personal ethics and limited use of technology contribute to errors in financial reporting. This study found that improving the quality of financial management requires discipline in routine documentation, strict cash segregation, and improved operational oversight